N-terminal pro-brain natriuretic peptide is a useful prognostic marker in patients with pre-capillary pulmonary hypertension and renal insufficiency. - Lars Harbaum (Public Library of Science (PLoS), 2014)
N-terminal pro-brain natriuretic peptide (NT-proBNP) is a routinely used prognostic parameter in patients with pre-capillary pulmonary hypertension (PH). As it accumulates in the presence of impaired renal function, the clinical utility of NT-proBNP in PH patients with concomitant renal insufficiency remains unclear. In a retrospective approach, patients with pre-capillary PH (group I or IV) and concomitant renal insufficiency at time of right heart catheterization (glomerular filtration rate (GFR) ≤60 ml/min/1.73 m2) were identified out of all prevalent pre-capillary PH patients treated at a single center. Forty patients with renal insufficiency (25.8%) were identified and matched regarding hemodynamic parameters with a control group of 56 PH patients with normal renal function (GFR >60 ml/min/1.73 m2). Correlations of NT-proBNP levels with hemodynamic and prognostic parameters (time to clinical worsening and overall survival) were assessed. Overall, GFR correlated inversely with NT-proBNP and had the strongest influence on NT-proBNP levels in a stepwise multiple linear regression model including hemodynamic parameters and age (r2 = 0.167). PH patients with renal insufficiency had significant higher levels of NT-proBNP (median: 1935 ng/l vs. 573 ng/l, p = 0.001). Nevertheless, NT-proBNP correlated with invasive hemodynamic parameters in these patients. Using higher cut-off values than in patients with preserved renal function, NT-proBNP levels were significantly associated with time to clinical worsening (>1660 ng/l, p = 0.001) and survival (>2212 ng/l, p = 0.047) in patients with renal insufficiency. Multivariate Cox's proportional hazards analysis including established prognostic parameters, age and GFR confirmed NT-proBNP as an independent risk factor for clinical worsening in PH patients with renal insufficiency (hazard ratio 4.8, p = 0.007). Thus, in a retrospective analysis we showed that NT-proBNP levels correlated with hemodynamic parameters and outcome regardless of renal function. By using higher cut-off values, NT-proBNP seems to represent a valid clinical marker even in PH patients with renal insufficiency.